2011
DOI: 10.1088/0031-9155/56/4/020
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo investigation of contaminant electrons due to a novelin vivotransmission detector

Abstract: A novel transmission detector (IBA Dosimetry, Germany) developed as an IMRT quality assurance tool, intended for in vivo patient dose measurements, is studied here. The goal of this investigation is to use Monte Carlo techniques to characterize treatment beam parameters in the presence of the detector and to compare to those of a plastic block tray (a frequently used clinical device). Particular attention is paid to the impact of the detector on electron contamination model parameters of two commercial dose ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…At smaller field sizes, the lack of phantom scatter resulted in a much lower field size factor, whereas for field size >10 Â 10 cm 2 , the higher contribution of the collimator scatter due to the shorter SDD resulted in a higher field size factor. Asuni et al 63 performed Monte Carlo studies on the contaminant electrons due to transmission detector. They found that the transmission detector increased the contaminant electrons at shorter SSD of 70 cm and increasing with larger field sizes.…”
Section: Iiif Field Size Dependencementioning
confidence: 99%
“…At smaller field sizes, the lack of phantom scatter resulted in a much lower field size factor, whereas for field size >10 Â 10 cm 2 , the higher contribution of the collimator scatter due to the shorter SDD resulted in a higher field size factor. Asuni et al 63 performed Monte Carlo studies on the contaminant electrons due to transmission detector. They found that the transmission detector increased the contaminant electrons at shorter SSD of 70 cm and increasing with larger field sizes.…”
Section: Iiif Field Size Dependencementioning
confidence: 99%
“…BEAMnrc=EGSnrc Monte Carlo code 19 was used to model the head of the linear accelerator based on a detailed description provided by the manufacturer for the 6 MV photon beam. This model has been previously validated 20 and found to be accurate. For this work, two phase-space files were obtained as shown in Fig.…”
Section: Iib1 Calculation Of the Film Response Functionmentioning
confidence: 94%
“…For phantoms constructed of water-like media, we express as , (6) where is the relative electron density averaged between point P and the ∆S center (however, it has been found [13][14][15] that the contamination dose does not vary simply in proportion to the beam water collision kerma of ).…”
Section: Dose Calculation Principlementioning
confidence: 99%
“…(d) h wedge and k wedge (used as θ wedge <π/2) in equations 1 and 2 are, respectively, , (13) , (14) where F wedge_p and F wedge_s are the correction factors, respectively, for the calculation of the primary and scatter dose components, not as a function of E N . We express them as ,…”
Section: Dose Calculation Principlementioning
confidence: 99%